Synthesis of anticancer drug anastrozole via phase-transfer catalyst - Quyen, Tran Ngoc; Hoang, Nguyen; Huong, Le Thi; Phuong, Nguyen Thi; Khoa, Nguyen Cuu (Vietnam Journal of Chemistry, 2015)
2, 2’-[5-(1H-1, 2, 4-triazol-1-ylmethyl)-1, 3-phenylene] bis (2-methylpropanenitrile) (anastrozole) is a novel non-steroidal drug exhibiting the inhibitory action of the enzyme aromatase which is currently used for the treatment of advanced breast cancer in post menopausal women.          Herein we introduce an effective method in synthesis of the drugs using phase-transfer catalyst (PTC). In the same condition, the yield of anastrozole increased in the order of DMF < toluene + benzakonium chloride (BKC) < toluene + tetrabutyl ammonium bromide (TBAB). Moreover, use of PTC in the reaction issued a highly selective method and high yield, resulting in reduction of isomeric impurity of anastrozole in the obtained product.